The predıctıon of dıffıcult ıntubatıon wıth bedsıde scorıng systems - Gerçek, Arzu; Lim, Sema; İşler, Banu; Eti, Zeynep; Yılmaz Göğüs (My University, 2003)
Objective: The aim of this study was to evaluate the correlation of sex, age, bedside scoring systems and body mass index with laryngoscopic view in patients with clinically difficult intubation.
Keywords: Intubation (Intratracheal), Difficult